THE DEVELOPMENT OF BASIC TECHNIQUES SEPAK TAKRAW EXERCISE WITH APPROACH PLAYING THE NOVICE ATHLETES. - Fajar Wahyu Edi (Sriwijaya University Learning and Education International Conference, 2018)
This research is for athletes novice especially sepak takraw sport. The number of samplestaken as many as 20 athletes novice at elementary school number 12 Talang KelapaBanyuasin. The development is done by using the basic needs analysis method of sepaktakraw, initial product design, expert validation, design improvement, small group trial,product revisions, large group trials, product revision and the final product. Techniques ofcollecting data using observation guidelines, questionnaire, and validity testing using t-Test (Pos Test and Post Test one group design). The result of pre test of big group ofsoccer technique through t test got result of T count = 15,118 with Df = 20 at significancelevel 5% (T table = 1,72472), because value of T count ˃ T table (15,118 ˃ 1,72472) pthis means the value of T test results arithmetic greater than T table. while the result ofpost test of T test in big group got result of T test count = 24,372 through significance 5%(T table = 1,72472) hence can be concluded there is increasing ability of soccer techniquefrom result of pre test to post test have difference of = 9,254 through significance of 5% Ttable = 1.72472. The result of pre test of big group of soccer technique through t test isgot result of T count = 11,466 with Df = 20 at significance level 5% (T table = 1,72472),because value of T arithmetic ˃ T table (11,466 ˃ 1,72472) p this means the value of Ttest results arithmetic greater than T table. while the result of post test of T test in biggroup got result of T test count = 17,601 through significance 5% (T table = 1,72472)hence can be concluded there is improvement of ability of soccer technique from result ofpre test to post test have difference of = 6,135 through significance of 5% T table =1.72472.The result of pre-test of large group of thigh base technique through t test is obtained by Tcount = 15,983 with Df = 20 at 5% significance level (T table = 1,72472), because thevalue of T arithmetic ˃ T table (15, 983 ˃ 1.72472 ) this means the value of T test resultis bigger than T table. while the result of post test of T test on big group got result of Ttest count = 24,498 through significance 5% (T table = 1,72472) hence can be concludedthere is improvement of thigh technique ability from result of pre test to post test havedifference of = 8,515 through significance of 5% T table = 1.72472.The result of pre test of big group of head technique through t test is obtained by Tcalculation = 11,979 with Df = 20 at 5% significance level (T table = 1,72472), becausethe value of T arithmetic ˃ T table (11,979 ˃ 1,72472) p this means the value of T testresults arithmetic greater than T table. while the result of post test of T test in big groupgot result of T test count = 24,498 through significance 5% (T table = 1,72472) hence canbe concluded there is improvement of capability of head technique technique from resultof pre test to post test have difference of = 12,519 through significance of 5% T table =1.72472